The Influence of Multimedia-Based Learning Media on Students' Learning Interest in Science Subjects in Grade V of Pannara Public Elementary School, Makassar City - Anjani; Fitriana, Eka; Suhardianto (Jurnal Mercusuar, 2021)
This study aims to determine the effect of multimedia-based learning media on students’ interest in science subjects for class V Pannara Elementary School in Makassar. This type of research is an experiment using a quantitative approach. This experimental research is classified into Pre-experimental For one group; the research sample is 31 students. The research instrument used was documentation, observation, questionnaires, and data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. In this study class V, the experimental class was given a pre-test using a questionnaire about the use of video learning multimedia. The results of the hypothesis test an alpha- (0, 05) significance level with the t-test showed that the value (0.000) with the criteria sig (0.000) < alpha 0.000 means H1 is accepted and H0 is rejected. So it can be concluded that there is an effect of using multimedia-based learning media on students’ interest in science subjects for fifth-grade students of Pannara Elementary School in Makassar.